Generation Y and employer brand : an exploratory study on what attracts them. - Woo, Mei Yi. (2013)
This research explores what employer brand means to Generation Y (Gen-Y) jobseekers in Singapore. The components of organisation reputation and job attributes are chosen to represent employer brand. Based on 187 responses collected for our survey, factor analysis is carried out to create the resulting six factors or types of employer brand that are attractive to these jobseekers. The three factors under the component of organisation reputation are Social Responsibility, Organisation Structure and Rewards, and Competitive Multinational Corporations (MNC), while the three factors under the component of Job Attributes are Employee Engagement, Employee Development, and Work-Life Balance. A cluster analysis is conducted on the eight personality aspects adopted to create three clusters or profiles of personality. Members of Cluster 1 are high in collectivism and low in neuroticism (collectivists with low neuroticism), members of Cluster 2 are high in self-efficacy and low in extraversion (introverts with high self-efficacy), and members of Cluster 3 are high in self-efficacy and low in external locus of control (the “go-getters”).